Pengaruh Bobot Telur Tetas Terhadap Daya Tetas dan Berat DOD (Day Old Duck) Bebek Hibrida di CV Anugerah Mulia Farm - Zannuar, M. Ivan; Andaruisworo, Sapta; Yuniati, Erna (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to determine the effect of hatching egg weight on the hatching power and DOD (Day Old Duck) weight of Hybrid Ducks and to determine the hatching egg weight that has the best hatching power and also the most optimal DOD weight. The potential need for duck meat that still cannot act as a mainstay animal food source is caused by the relatively low productivity in Indonesia. Hybrid ducks are ducks that are a cross between Peking and Khaki Campbell ducks. The DOD weight produced determines the quality of the hybrid ducklings to be cultivated. This research was conducted at CV. Anugerah Mulia Farm, Ngledok Hamlet, Mojokrapak Village, Tembelang District, Jombang Regency from June to November 2024. The object of this study used 90 Hybrid Duck hatching eggs. This study used the RAL (Complete Randomized Design) method with 3 treatments and 6 replications. Each treatment used 5 hatching eggs. The parameters taken in this study were the hatching power and DOD weight of Hybrid Ducks. The results of the data obtained were analyzed using the IBM SPSS version 26 application with Analysis of Variance (ANOVA) and continued with the Duncan Multiple Range Test (DMRT). The results obtained from this study showed that egg weight had a significant effect (P <0.05) on the hatchability of Hybrid Ducks by 90% (P1) and the highest DOD weight at P1 was 50.48 grams.